Distribusi Horizontal Burung di Kawasan Ekowisata Mangrove Bagek Kembar, Lombok Barat - Sri Aprilia Nur Larasati; Gito Hadiprayitno; Prapti Sedijani; I Wayan Suana; Eni Suyantri (Bioscientist : Jurnal Ilmiah Biologi, 2025)
This study aims to determine the horizontal distribution of birds based on habitat type, namely fish ponds, rehabilitated mangroves, and natural mangroves, located in the Bagek Kembar Mangrove Area. Observations were conducted in June-July at the Bagek Kembar Mangrove Area, Sekotong. This research uses a transect method, following the paths found at three observation locations. Bird observations were conducted twice, in the morning (06:30-09:30 WITA) and evening (15:30-18:30 WITA). The results recorded 57 species, with the dominant habitat for finding bird species being the natural mangrove area, which has a fairly dense and diverse vegetation structure. The horizontal distribution of birds in the Bagek Kembar Mangrove Area is illustrated using CANOCO for Windows 4.5 with a PCA (Principal Component Analysis) diagram. This study concludes that bird diversity is higher in natural mangrove habitats compared to fishpond and rehabilitated mangrove habitats, making this area important for supporting conservation and the development of birdwatching ecotourism.